The Intellectuals And Socialism - Hayek, Friedrich August von (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2017)
In this article, Hayek investigates the "secondhand dealers on ideas", examining the existing incentives and characteristics of the proponents of intellectual activity. In addition to providing an explanation why intellectuals tend to socialism, the author suggests that classical liberal intellectuals should emulate the pursuit of these socialist intellectuals for desirable rules, different from the status quo, to construct a liberal alternative that captivates consumers of political ideas.